The Effect of Knowledge of Entrepreneurship, Family Environment, Independence on Interest in Entrepreneurship with the Income Expectations as Moderating Variables (Universitas Negeri Semarang, 2022)
Interest in entrepreneurship was an interest that shows up in person to make entrepreneurial a career choice. This study aimed to test whether there was an effect of knowledge of entrepreneurship, family environment, and independence on interest in entrepreneurship with income expectations as moderating variables in FEB students of Universitas Negeri Makassar. The population in this study was students of the Faculty of Economics and Business at Universitas Negeri Makassar class of 2018 and 2019, which amounted to 1.340 students and was collected using the cluster proportional random sampling technique that obtained 308 respondents. The data collecting technique in this study was using a questionnaire. The data analysis technique used was descriptive statistical analysis and moderated regression analysis. The results showed that the variables of knowledge on entrepreneurship and independence had a positive and significant effect on the interest in entrepreneurship; meanwhile, the variables of family environment had no significant impact on the interest in entrepreneurship. Besides that, variables of income expectations can be used to moderate the effect of knowledge of entrepreneurship on the interest in entrepreneurship. However, the income expectations had failed to negotiate the impact of family environment and independence on the interest in entrepreneurship. This study had expected to enrich the wealth of knowledge and test the Theory of Planned Behavior (TPB) related to the interest in entrepreneurship as well as the basics of policy on the educational side, especially entrepreneurship education, as the guide in the development of interest in entrepreneurship.